2003
DOI: 10.1074/jbc.m211144200
|View full text |Cite
|
Sign up to set email alerts
|

NMR Study of Mersacidin and Lipid II Interaction in Dodecylphosphocholine Micelles

Abstract: Mersacidin belongs to the type B lantibiotics (lanthi-onine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
119
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 49 publications
1
119
0
1
Order By: Relevance
“…Mersacidin forms a tightly associated 1:1 complex with Lipid II, and nisin sequesters Lipid II via encapsulating the pyrophosphate of Lipid II within a hydrogen bond network formed by nisin backbone amides (36,37). The nisin-Lipid II complex organizes into a supramolecular pore-like assembly, engendering a breach in membrane integrity and leading to cell death by osmotic lysis (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Mersacidin forms a tightly associated 1:1 complex with Lipid II, and nisin sequesters Lipid II via encapsulating the pyrophosphate of Lipid II within a hydrogen bond network formed by nisin backbone amides (36,37). The nisin-Lipid II complex organizes into a supramolecular pore-like assembly, engendering a breach in membrane integrity and leading to cell death by osmotic lysis (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…1) (17,18,29,30). Importantly, the six-aminoacid-containing MeLan B-ring in Hal␣, which is believed to be important for lipid II binding in mersacidin's C-ring (32), is conserved including the invariant and essential Glu within this ring (33). This MeLan ring is also found in the ␣͞A1-peptides of lacticin 3147 (21), plantaricin W (17), staphylococcin C55 (18), Smb (29), and BHT-A (30), as well as in the A-ring of the lacticin 481 subgroup of single component lantibiotics (3).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the mode of action of lantibiotics, this speculation seems to be reasonable. It has been shown that several lantibiotics, including nisin (11,14), LtnAI (␣-peptide of lacticin 3147) (38), and mersacidin (3,13), use lipid II, a cell wall precursor located on the membrane, as a docking molecule. After docking, these lantibiotics form pores on the cytoplasmic membrane and/or inhibit cell wall biosynthesis.…”
Section: Discussionmentioning
confidence: 99%